Quality, Storage Stability, and Effect of Cryoprotectants onUltrastructure of Superchilled Chicken - Banerjee, Rituparna; Maheswarappa, Naveena B; Muthukumar , M; Dasoju, Sowmya (Journal of Meat Science, 2024)
The concept of superchilling, an alternative to traditional chilling and freezing methods, is to reduce the temperature 1-2 °C below the initial freezing point of the food enabling safe, and high-quality product. This work was aimed to explore the effects of superchilling (-2±0.5°C), chilling (4±1°C), and freezing (−18±1°C) on the quality and storage stability of dressed chicken and also to evaluate the role of cryoprotectants during superchilling for enhanced meat quality. In superchilled samples, improved water holding capacity (WHC) and lower shear force values were observed relative to frozen chicken. SDS-PAGE analysis revealed the appearance of 29 kDa protein bands in superchilled samples on 7th and 14th day, indicating troponin degradation and tenderization. Scanning electron microscopy (SEM) studies indicated minimal damage to muscle fibre ultrastructure in superchilled chicken relative to frozen samples. Integrity of fibre structure was well maintained in superchilled samples treated with sorbitol as a cryoprotectant relative to sucrose and polyphosphate. Results demonstrated the potential use of superchilling process along with cryoprotectants for improved quality and enhanced shelf-life of chicken.